INTERACTIVE METHODS, FORMS AND TECHNIQUES OF TEACHING IN THE CLASSROOM - Alibekova Ra`na Khudoyberdiyevna (Web of Journals Publishing, 2024)
In this article, the author describes interactive learning, its content and essence. The article also provides an overview of interactive methods such as carousel, dialogue, and many others. special attention is paid to the issue of freedom of choice of the type of educational activity in interactive training.
Keywords: 3D learning, reflectivity, self-activation, creativity, positive, interactive, brainstorming”, “case analysis”.